Dynamics of indicators of physical health among students engaged in power exercises. - Magliovanyy A.V; Shymechko I.M; Boyarchuk A.M; Moros E.I (Kharkov National Pedagogical University, 2011)
The research of level and dynamics of physical health of students (17-22 years old, n=36), which were additionally engaged in power exercises in the university sections (for example of section from weight sport), by the express method of estimation of health, offered G.L. Apanasenko; the comparison of finding data with the indexes of students, which got busy after the operating system of physical education are considered in the article. It is definite, that employments by exercises with weights positively affect physical development, functional state and health level of students in the process of education.